PRAKTIK JURNALISTIK DALAM PROGRAM EKSTRAKURIKULER JURNALISTIK DI MADRASAH ALIYAH NEGERI 2 TANAH DATAR - Okditazeini, Vannyora; Marzal, Novrizon; Salma, Zakiati; Arsa, Yulia; Purnama, Hanifan (Jurnal Ranah Komunikasi, 2024)
This study aims to analyze the practice of journalism in the extracurricular activities at MAN 2 Tanah Datar. Using a constructivist paradigm, the research adopts a qualitative approach with a case study method. Data collection techniques include in-depth interviews with supervisors and participants of the journalism extracurricular activity, direct observation of journalistic practices, and analysis of journalistic works produced by the students. Supporting data were obtained through literature reviews and online searches to provide a theoretical context. The findings reveal the processes involved in news production and dissemination within the extracurricular activity, highlighting the challenges faced and the social interactions between participants, supervisors, and other stakeholders. Data analysis was conducted interactively, beginning with data reduction, systematic presentation, and concluding with key insights validated through triangulation methods. This study provides a comprehensive understanding of how journalistic culture is developed and practiced within an educational institution, emphasizing the importance of collaboration and overcoming barriers in nurturing student journalistic competencies.